Effect of Convective, Diffusive and Source Terms in Self Generated Magnetic Field due to Laser Plasma Interactions - Khanal, S.; Khanal, R (Himalayan Physics, 2015)
Laser-plasma interaction phenomenon has various applications and the most important one is in the Inertial confinement Fusion. Spatial and temporal variations of self generated magnetic field have been studied within the framework of magneto hydrodynamics. The evolution equation that describes the generation of magnetic field is solved using complex Fourier and Laplace transformation methods as an initial value problem. Convective, diffusive and source terms are considered in the evolution equation and are solved theoretically. Magnetic fields of the order of megagauss have been obtained among which the maximum field is just about 40 MG. The results are comparable with earlier reported results. The Himalayan Physics Year 5, Vol. 5, Kartik 2071 (Nov 2014) Page: 27-30